Effectivity and applicability of the German DEGRO/DGK-guideline for radiotherapy in CIED-bearing patients - Gauter-Fleckenstein, Benjamin; Barthel, Christoph; Büttner, Sylvia; Wenz, Frederik; Borggrefe, Martin; Tueluemen, Erol (Radiotherapy and oncology, 2020)
Background and purpose - No evidence has been presented until now whether recommendations given in recently issued guidelines concerning CIED-bearing patients significantly decrease RT-related complications. - Materials and methods - 160 RT-cases were prospectively treated with 3D-CRT, IMRT, SBRT using exclusively 6 MV photons (n = 146) and electrons (n = 14) according to the 2015 issued German DEGRO/DGK-guideline for CIED-bearing patients and compared to 40 RT-cases (3D-CRT, 10-23 MV photons (n = 39) and electrons (n = 1)) of CIED-bearing patients which were treated in concordance to the 1994 issued AAPM-guideline. - Results - With AAPM-recommendations, complications occurred in 7/39 (17.95%) photon-RT cases, one patient experienced inadequate defibrillation therapy. For all patients treated with photon energies between 6 and 23 MV, a relative risk for CIED failure if treated with > 6 MV was calculated to be 9.03 (95% CI 5.24-15.55). After implementation of the DEGRO/DGK guideline, no complications were noted in 147 cases treated with photons, even though CIED-doses were as high as 5.37 Gy. In 13 cases treated with electrons, one PM lost patient-related data in a patient receiving antiproliferative RT to mammary glands. - Conclusions - Implementation of the German DEGRO/DGK-guideline effectively prevented radiation-associated CIED failures in patients treated with photons. Limitation of photon energy to 6 MV, suspension of defibrillation therapy in ICDs, surveillance of patients according to risk stratification and avoidance of direct irradiation of CIEDs should become standard of care.
Gesehen am 05.06.2024